Experimental and theoretical studies on the mechanical and structural changes imposed by the variation of clay loading on poly(vinyl alcohol)/cloisite® 93A nanocomposites. Issue 2 (10th August 2018) - Kabalan, Lara; Zagho, Moustafa M.; Al‐Marri, Mohammed J.; Khader, Mahmoud M.
Abstract : Polymer nanocomposites (PNC) structures are promising materials due to their novel properties. However, many of their characteristic physical, mechanical, and chemical behavior have not been quantified. Depending on the interface interactions between polymeric chains and clay sheets, various classes of polymer/clay nanocomposite exist: Intercalated, flocculated and exfoliated nanocomposites. In this work, we present an experimental study of poly(vinyl alcohol) (PVA)‐cloisite® 93A followed by a classical molecular dynamic (MD) simulations. The structural properties of the system were studied using X‐ray diffraction (XRD), nanoscanning electron microscopy (NSEM). Both revealed intercalation between PVA chains and cloisite® 93A nanoclay. Another evidence of the intercalation between PVA and cloisite® 93A nanoclay was realized from the differential scanning calorimetry (DSC) which confirmed as surge in crystallinity upon intercalation. A main focus for the intercalated structure was to investigate the impact of nanofillers content on the mechanical performance. Intercalation significantly influenced both Young's modulus and the % of elongation of PVA/cloisite® 93A blends. Young's modulus and tensile stress were raised with the content of the filler content up to 3 wt%. For higher content, opposite observations are addressed owing to the formation of aggregates of nanofillers and as consequence construction of microvoids. From the MD simulations, the intercalation has been shown by the increase of the d‐spacing with the clay loading. By calculating the density profile, it has been demonstrated that in case of low clay loading, the cloisite® 93A has its nitrogen groups on the clay surface and the long tails form layers. For the high loading of clay, nitrogen and carbon groups are together on the surface. Young modulus calculated theoretically follows the same experimental trend where an increase of the values has been observed with a clay loading up to 3 wt%, followed by a decrease of the values for higher clay loading. J. VINYL ADDIT. TECHNOL., 25:172–181, 2019. © 2018 Society of Plastics Engineers